Complex, intelligent, and software intensive systems : proceedings of the 13th International Conference on Complex, Intelligent, and Software Intensive Systems (CISIS-2019) /: proceedings of the 13th International Conference on Complex, Intelligent, and Software Intensive Systems (CISIS-2019). ([2019]) - Unknown
No abstract available